Association between the levels of blood platelet indicators and the severity of knee osteoarthritis (radiologic and clinical) - الدو كاسر; زريق يوسف; هيفا أريج (Latakia University Journal -Medical Sciences Series, 2022)
Objective:This study aims to investigate the relationship between platelet indices, and radiological and clinical disease severity in patients with primary osteoarthritis of the knee Methods: Analytic study (Corss-secctional), the research sample included 83 patients (24 males, 59 females) with primary osteoarthritis in the knee joint, the ages of the research sample patients ranged between 40 to 60 years, a detailed history was taken for each patient, and a comprehensive clinical examination of active and passive joint movements was performed with clinical assessment according to the clinical Western Ontario and MacMaster Universities score (WOMAC), and the weight and height of each patient were measured, BMI (kg/m2) was calculated, as well as a complete blood count (CBC), sedimentation rate (ESR), and C protein Reactive (CRP), a simple radiograph of the knee joints anterior to posterior and lateral and the determination of the Kellgren-Lawrence score (K-L) were performed, Results: The results showed that about two thirds of the study sample had mild to moderate OA according to WOMAC clinical assessment index and KL radiographic index. We note that there is a significant statistical relationship between BMI and WOMAC index and K-L index, which was higher in the severe group. We note significant differences for MPV between the two groups of patients as per radiographic evaluation which were higher in the severe group. It was noticed that there is a statistically significant increase for MPV between the two groups of patients according to their radiological assessment in the severe group, according to the different values of fields` BMI. It wasn’t observed a statistically significant relationship between other platelet indices and the radiological and clinical severity of osteoarthritis in the knee joint according to the demographic factor. Conclusion: Mean platelet volume (MPV) maybe considered as an important indices of the radiological progression of primary osteoarthritis of the knee joint.